RCN4GSC Workshop Report: Modeling a Testbed for Managing Data at the Interface of Biodiversity and (Meta)Genomics, April 2011. Issue 1 (July 2012) - Robbins, Robert; Cochrane, Guy; Davies, Neil; Dawyndt, Peter; Kottmann, Renzo; Krishtalka, Leonard; Morrison, Norman; Tuama, Éamonn; San Gil, Inigo; Wooley, John
Abstract At the GSC11 meeting (4–6 April 2011, Hinxton, England, the GSC's genomic biodiversity working group (GBWG) developed an initial model for a data management testbed at the interface of biodiversity with genomics and metagenomics. With representatives of the Global Biodiversity Information Facility (GBIF) participating, it was agreed that the most useful course of action would be for GBIF to collaborate with the GSC in its ongoing GBWG workshops to achieve common goals around interoperability/data integration across (meta)-genomic and species level data. It was determined that a quick comparison should be made of the contents of the Darwin Core (DwC) and the GSC data checklists, with a goal of determining their degree of overlap and compatibility. An ad-hoc task group lead by Renzo Kottman and Peter Dawyndt undertook an initial comparison between the Darwin Core (DwC) standard used by the Global Biodiversity Information Facility (GBIF) and the MIxS checklists put forward by the Genomic Standards Consortium (GSC). A term-by-term comparison showed that DwC and GSC concepts complement each other far more than they compete with each other. Because the preliminary analysis done at this meeting was based on expertise with GSC standards, but not with DwC standards, the group recommended that a joint meeting of DwC and GSC experts be convened as soon as possible to continue this joint assessment and to propose additional work going forward.